2019
DOI: 10.14814/phy2.14094
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness during whole‐body passive heat stress in healthy older adults

Abstract: We tested the hypothesis that whole‐body passive heat stress reduces arterial stiffness in older adults. At preheat stress (baseline) and when core temperature was elevated by 0.6 ± 0.2°C (mild) and 1.2 ± 0.3°C (moderate), arterial stiffness was measured in eight healthy younger (26 ± 5 years) and eight healthy older (70 ± 4 years) adults in the supine position. Arterial stiffness was estimated from carotid‐to‐femoral pulse wave velocity (cf PWV , applanation tonometry). cf P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…Despite the ≥3‐fold increases in blood velocity, no changes were seen in wave speed or arterial distensibility. The present findings of local stiffness are in agreement with past whole body and two leg hyperthermia studies which reported no changes in regional (carotid–radial) arterial stiffness (Ganio et al, 2011 ; Moyen et al, 2016 ; Schlader et al, 2019 ). However, studies exploring the recovery following hyperthermia, reported decreases in peripheral and/or leg (femoral–ankle region) arterial stiffness alongside an elevated core temperature (Caldwell et al, 2017 ; Cheng et al, 2021 ; Lee et al, 2018 ; Sugawara & Tomoto, 2021 ; Thomas et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the ≥3‐fold increases in blood velocity, no changes were seen in wave speed or arterial distensibility. The present findings of local stiffness are in agreement with past whole body and two leg hyperthermia studies which reported no changes in regional (carotid–radial) arterial stiffness (Ganio et al, 2011 ; Moyen et al, 2016 ; Schlader et al, 2019 ). However, studies exploring the recovery following hyperthermia, reported decreases in peripheral and/or leg (femoral–ankle region) arterial stiffness alongside an elevated core temperature (Caldwell et al, 2017 ; Cheng et al, 2021 ; Lee et al, 2018 ; Sugawara & Tomoto, 2021 ; Thomas et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, hyperthermia may directly act on the conduit artery supplying blood to the heated region by increasing arterial stiffness/decreasing arterial distensibility rather than altering diameter, as seen during incremental exercise (Pomella et al, 2018 ). The current literature suggests that central and/or regional arterial stiffness is unchanged during acute hyperthermia (Ganio et al, 2011 ; Moyen et al, 2016 ; Schlader et al, 2019 ) and declines following the cessation of heating (Lee et al, 2018 ; Sugawara & Tomoto, 2021 ; Thomas et al, 2017 ). To our knowledge, however, no study has explored the effects of hyperthermia on arterial distensibility using local techniques—such as the PU ‐loop or ln( D ) U ‐loop (Feng & Khir, 2010 ; Khir et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with our findings (Fig. 2), changes in AS during heat stress are dependent on the magnitude of baseline stiffness (ie, inversely related) 38 ; thus, greater benefit would be anticipated in the lower fit firefighters who exhibited elevated resting stiffness and in whom reductions in AS were observed. However, it should be noted that heat stress during moderate intensity cycling exercise was not demonstrated to acutely change AS in middle-aged individuals 37 .…”
Section: Discussionsupporting
confidence: 88%
“…This intervention evoked 0.5, 1.0, and 1.5°C elevation in core temperature from pre-heat-stress baseline for 36 ± 5, 60 ± 11, and 77 ± 15 min of exposure, respectively, but they did not induce significant changes either in aortic or leg PWV. Likewise, Schlader et al (2019) found no significant change in central arterial stiffness in older adults during whole-body heating by 49°C water and 1.3°C of core temperature elevation (approximately 18 min). Passive heat stress is accompanied by sympathetic activation, dehydration, and elevation of blood viscosity that may mask arterial destiffening ( Low et al, 2011 ; Gagnon et al, 2015 ; Stojadinovic et al, 2015 ).…”
Section: Introductionmentioning
confidence: 75%